Young Man With Abdominal Pain - An Interactive Case Exercise - John Woosley; Claudia Brady; Kirsten Boland (Association of American Medical Colleges, 2010)
Abstract This educational module covers the clinical, radiographic, pathologic, and therapeutic aspects of acute appendicitis. The single-page case exercise uses the roll-over menu and click button functionality of Articulate Engage '09 software to enable students to work through the case at their own pace, in a nonlinear fashion. Students are able to access case details such as, clinical history, physical examination, laboratory data, radiology information, gross pathology (i.e., a video recording of a dissection of the patient's appendix), and histopathology data (i.e., annotated and narrated high-magnification images). By allowing students to view additional hidden details in any order, the case is intended to foster clinical decision-making skills. The case exercise includes a series of questions that the student should try to answer before reading the case summary. The case summary details critical learning points and addresses the questions that have been posed to the student.